Depression classification with MDD (Major Depressive Disorder) using signal processing and machine learning - Saleque, Shahriar; Spriha, Gul-A-Zannat; Kamal, MD Rasheeq Ishraq; Khan, Rafia Tabassum (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.